Oxidação de metano a metanol sobre zeólitas Cu.MOR: efeito do método de preparação na atividade catalítica - Picinini, Monize (Universidade Federal de São Carlos, 2019)
The direct oxidation of methane to higher value-added products, such as methanol, has gained notable interest in recent times. The challenge is that this process occurs with high efficiency and lower energy consumption, thus becoming economically interesting. Due to the difficulty in breaking the C-H bonds of methane, it was required to employ catalysts active and selective to methanol. Thus, the researches have been directed to the use of zeolites exchanged with oxo-cations species (M-O-M)2+, responsible for the oxidation of methane, recreating a mechanism of reactivity similar to that found in the enzyme methane monooxygenase. In this context, this work had as objective to oxidize methane to methanol on Cu.mordenite zeolites with different Si/Al ratios, which were prepared by ion exchange or impregnation method. The samples were characterized by X-ray fluorescence, X-ray diffraction, nitrogen physisorption, scanning electron microscopy, hydrogen temperature-programmed reduction, Raman spectroscopy, and diffuse reflectance ultraviolet-visible spectrophotometry. The oxidation of methane was carried out in three steps: activation of Cu.mordenite zeolites under air flow, reaction with methane and extraction of the generated methanol adsorbed on the zeolite. The influence on the catalytic activity of the preparation method, content, and type of copper species and Si/Al ratio were analyzed. All the zeolites studied were able to convert methane to methanol, however, those prepared by ion exchange showed higher production than those prepared by impregnation. The maximum production obtained, with a value of 15.61 μmol of methanol.gcat-1 is in the order of results found in the literature. Based on the methanol production and characterization data, it was possible to confirm that the presence of oxidized copper species occupying charge compensation sites in the zeolite was a determining factor in their activity, whereas the copper oxide formation did not present activity. As expected, methanol production increased with the addition in copper content, however, increased with the Si/Al ratio of the zeolite. Under the conditions used, it was not possible to identify the copper oxo-cations species by the DRS-UV-Vis and Raman spectroscopy techniques.
Oxidation of methane to methanol over Cu.MOR zeolites: effect of the preparation method on catalytic activity
Keywords: Metano; Metanol; Zeólita mordenita; Oxo-cátions de cobre; Methane; Methanol; Mordenite zeolite; Copper oxo-cations; ENGENHARIAS::ENGENHARIA QUIMICA